Health, well-being and lifestyle from a gender perspective - Blesa Matienzo, María Dolores (2020)
This article deals with the issue of health from the point of view of well-being and lifestyle, we propose that the well-being of people can be achieved through our way of acting, considering important the health of women in particular. In the review of studies regarding well-being, we have included topics related to social exclusion, women’s health, medicalization, the relationship between health and sickness and the gender differences that exist in our societies.